Predicting Sustainable Consumption Behavior among Generation Z: Role of Nature Relatedness and Environmental Concern - Somad, Kemas Mohd. Saddam Abd.; Fatmasari, Agustin Erna (UI Scholars Hub, 2024)
Unsustainable consumption is at the root of many current environmental issues, including global warming, waste pollution, and biodiversity loss. It is therefore important to identify the predictors of sustainable consumption, particularly among Generation Z, the largest age cohort in the current population of Indonesia. This research aimed to investigate the association between nature relatedness, environmental concern, and sustainable consumption behavior among Generation Z in Semarang City. A total of 140 participants were involved in this research through convenience sampling. Instruments that were used are the Sustainable Consumption Behaviour scale (19 items; α=0.841), the Nature Relatedness scale (24 items; α=0.904), and the Environmental Concern scale (24 items; α=0.878). The data was analyzed with the hierarchical multiple regression technique using SPSS version 29.0.1.1 software. The findings reveal that nature relatedness and environmental concern positively predict sustainable consumption behavior (β=.275, p